2018
DOI: 10.3386/w24867
|View full text |Cite
|
Sign up to set email alerts
|

Location as an Asset

Abstract: The location of individuals determines their job opportunities, living amenities, and housing costs. We argue that it is useful to conceptualize the location choice of individuals as a decision to invest in a 'location asset.' This asset has a cost equal to the location's rent, and a payoff through better job opportunities and, potentially, more human capital for the individual and her children. As with any asset, savers in the location asset transfer resources into the future by going to expensive locations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Including a concave housing supply and heterogeneous expenditure shares on housing across skill groups also reinforces the dynamic of immobile, low skilled workers accumulating in economically depressed places. More low skilled workers choose to live in economically depressed places because they benefit more from inexpensive rents (Notowidigdo, 2011;Ganong and Shoag, 2017;Bilal and Rossi-Hansberg, 2018). And inexpensive rents arise because of the inelastic supply of already built housing in an area with weak demand for housing from high skilled workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including a concave housing supply and heterogeneous expenditure shares on housing across skill groups also reinforces the dynamic of immobile, low skilled workers accumulating in economically depressed places. More low skilled workers choose to live in economically depressed places because they benefit more from inexpensive rents (Notowidigdo, 2011;Ganong and Shoag, 2017;Bilal and Rossi-Hansberg, 2018). And inexpensive rents arise because of the inelastic supply of already built housing in an area with weak demand for housing from high skilled workers.…”
Section: Discussionmentioning
confidence: 99%
“…1 In terms of policy impacts, several papers have shown that place-based policies can be ineffectual because equilibrium dynamics tend to undo their effects (Glaeser and Gottlieb, 2008 Local ties explain why people continue to live in economically depressed places. Other studies have claimed that people live in depressed places because inexpensive housing attracts people with low incomes (Notowidigdo, 2011;Ganong and Shoag, 2017;Bilal and Rossi-Hansberg, 2018). Local ties can also explain why the people who live in depressed places were often born in those places.…”
Section: Introductionmentioning
confidence: 99%
“…Crack-affected neighborhoods may have experienced neighborhood stigma and a negative reputation, given the disproportionately negative impact on black neighborhoods (Agar, 2003) and the reinforcement of negative stereotypes linking blacks and criminalization during the crack epidemic (Alexander, 2012). Individuals who originate from disadvantaged neigh- Alternatively, the crack epidemic may have induced selective migration flight to the suburbs, as a response to re(location) of employment opportunities (e.g., job suburbanization), which may have been affected by the crack epidemic; hence greater economic returns to cityto-suburb migration among selective minorities who can invest and transfer their resources to the future (e.g., employment opportunities in the suburbs) (Bilal and Rossi-Hansberg, 2018).…”
Section: The Crack Epidemic and City-to-suburb Mobilitymentioning
confidence: 99%
“…The idea that locations differ in the future opportunities that they offer was recently formalised in Bilal and Rossi-Hansberg (2020), who argue for the existence of dynamic gains from location on the basis that ruling them out implies implausibly large migration costs given the geographical differences in lifetime income and outcomes observed in the US. Also in the US context, Martellini (2019) shows that the well-established 'city-size wage premium' grows with years of experience, as the benefits of knowledge spill-overs become compounded over time.…”
Section: Local Labour Market Opportunitiesmentioning
confidence: 99%